Overview and Recent Challenges [In Africa Agriculture Trade Monitor 2024] - Odjo, Sunday; Zaki, Chahir; Traoré, Fousseini; Hebebrand, Charlotte (International Food Policy Research Institute, 2024)
The Africa Agriculture Trade Monitor (AATM) is an annual flagship publication of the International Food Policy Research Institute (IFPRI) and AKADEMIYA2063. This seventh edition provides an overview of short- and long-term trends and drivers behind Africa’s global trade, intra-African trade, and trade within Africa’s regional economic communities (RECs), with a focus on the nexus of trade and climate change. The six chapters of this 2024 AATM report are as follows. This first chapter offers an overview of the food security concerns in African countries in the wake of the global crisis related to the COVID-19 pandemic, the Russia–Ukraine war, and the global resurgence of protectionist policies. It examines trade through a food security lens, including availability, utilization, accessibility, and stability of food supplies, as well as the effects of tariffs, nontariff measures (NTMs), and deep trade agreements on food security in Africa. Special attention is paid to fertilizers, given the importance of these inputs for agricultural productivity and food security. As a result of Africa’s heavy dependence on fertilizer imports, farmers, and particularly smallholders, were severely challenged in the recent crisis when spikes in international fertilizer prices were compounded by high rates of domestic inflation.